Investigation of glass forming ability, crystallization behavior, and soft magnetic properties of Fe–B–P–C–Cu alloy ribbons. (October 2022) - Li, Yuluo; Shen, Ningning; Chen, Li; Lv, Kuang; Hui, Xidong
Abstract: The effect of Cu content on GFA, crystallization behavior, and soft magnetic properties in high P Fe84+x B6 P6 C3 Cu1−x (x = 0, 0.2, 0.4, 0.6, and 1.0 at. %) alloy ribbons were systematically investigated to balance the relationship between glass forming ability (GFA), heat treatment window, and soft magnetic properties of high saturation magnetic flux density ( B s ) Fe-based nanocrystalline alloys. It was discovered that lowering Cu promotes the formation of an amorphous structure. The GFA of alloys rises from 23 μm for Fe84 B6 P6 C3 Cu1 to 29 μm for Fe84.4 B6 P6 C3 Cu0.6 . Analysis of thermal physical properties shows that when Cu content is between 1.0 at. % and 0.6 at. %, reducing Cu in the alloys does not affect the onset temperature of the first crystallization peak ( T x1 ), the second one ( T x2 ), and Δ T (Δ T  =  T x2  −  T x1 ), whereas when Cu content is less than 0.6 at. %, reducing Cu leads to an increase in T x1 and a decrease in T x2 and Δ T, which is not conducive to obtaining a wide temperature range of precipitation of a single α-Fe phase. The alloys have a wide range of crystallization annealing temperature (693–753 K) and annealing time (60–6 min) to obtain a low coercivity ( H c ) of about 8.0 A/m, high B s of about 1.80 T, and high effective magnetic permeability ( μ e ) of about 10000 when Cu is between 1.0 at. % and 0.6 at. %. The B s, H c, and μ e of Fe84.4 B6 P6 C3 Cu0.6 alloy annealed at 723 K for 30 min are 1.82 T, 8.1 A/m, and 10820, respectively. Highlights: Low GFA of Fe–B–P–C–Cu alloy with high P (6 at. %) can be solved by Cu tuning. Annealing time of Fe84-84.4 B6 P6 C3 Cu1-0.6 alloys can be extended to 60 min. Fe84.4 B6 P6 C3 Cu0.6 alloy achieves the balance between magnetic properties and annealing.